2017
DOI: 10.1007/11157_2017_4
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Volcano Surveillance and Community Awareness in the Lead-Up to the 1994 Eruptions at Rabaul, Papua New Guinea

Abstract: Instrumental volcano surveillance and community awareness played key roles in preparing for the outbreak of the 1994 VEI 4 volcanic eruptions at Rabaul (pop. 17,000). The eruptions were preceded by 23 years of fluctuating unrest involving swarms of caldera earthquakes (max M L 5.2) and co-seismic uplift of parts of the floor of Rabaul Caldera. Eruption contingency planning was formally driven by government authorities and involved all sections of the community. Community awareness of the volcanic threat was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Large magmatic-hydrothermal systems buffer incoming magma intrusions, and then show unrest in repeated episodes before they finally erupt again. Petrologic evidence for repeated intrusions before the VEI 7 Minoan eruption of Santorini (Druitt et al, 2012), be- Table 3. fore smaller recent eruptions at Rabaul (Bouvet de Maisonneuve et al, 2015), and instrumentally monitored unrest at Rabaul and Campi Flegrei (Acocella et al, 2015;McKee et al, 2017) reflect such buffering.…”
Section: Short-range (Immediate) Forecastingmentioning
confidence: 94%
See 1 more Smart Citation
“…Large magmatic-hydrothermal systems buffer incoming magma intrusions, and then show unrest in repeated episodes before they finally erupt again. Petrologic evidence for repeated intrusions before the VEI 7 Minoan eruption of Santorini (Druitt et al, 2012), be- Table 3. fore smaller recent eruptions at Rabaul (Bouvet de Maisonneuve et al, 2015), and instrumentally monitored unrest at Rabaul and Campi Flegrei (Acocella et al, 2015;McKee et al, 2017) reflect such buffering.…”
Section: Short-range (Immediate) Forecastingmentioning
confidence: 94%
“…Experience from unrest and smaller eruptions at Rabaul (1979Rabaul ( -1994McKee et al, 2017), Campi Flegrei (1500s and ca. 1950Acocella et al, 2015;Chiodini et al, 2016;Kilburn et al, 2017), and Pinatubo (1990Newhall and Punongbayan, 1996a, and papers therein) also showed that despite prolonged early unrest, the final runup to eruption was just hours to days.…”
Section: Short-range (Immediate) Forecastingmentioning
confidence: 99%
“…The eruptions can be divided into two phases: Phase 1 -September 1994 to April 1995; Phase 2 -late November 1995 onward. Detailed accounts and analysis of Phase 1 and parts of Phase 2 have been documented in GVN (1994), Blong and McKee (1995), Bouvet de Maisonneuve et al (2015), McKee et al ( , 2017, and McKee (unpublished data). Eruptions at both sites produced identical dacites but the compositions of Tavurvur eruptives extended to mafic andesites.…”
Section: The Eruptions That Started In 1994mentioning
confidence: 98%
“…Tavurvur and the other near Vulcan, at about 3 am on 18 September 1994 (GVN, 1994;McKee et al, 2017). The following 27 hours included a period of sustained strong caldera seismicity and massive ground deformation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation